Group counseling services in reducing anxiety levels among drug rehabilitation residents: a humanistic qualitative inquiry - Nabilatul Urfah; Rahmad; Miftahuddin; Listiawati Susanti; Suhaimi (Southeast Asian Journal of Technology and Science, 2026)
Anxiety is a common psychological challenge experienced by residents undergoing drug rehabilitation, often hindering engagement in treatment and increasing vulnerability to relapse. Although group counseling is widely implemented in rehabilitation settings, limited qualitative evidence explains how residents experience this intervention and the mechanisms through which it alleviates anxiety. This qualitative descriptive study aimed to explore how group counseling services contribute to anxiety reduction among residents in a drug rehabilitation facility. Guided by a humanistic counseling perspective, the study involved one addiction counselor and five rehabilitation residents selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using Miles, Huberman, and Saldaña’s interactive analytic framework involving open, axial, and selective coding. Methodological integrity was enhanced through source triangulation and member checking. The findings revealed five interconnected themes: (a) multifaceted manifestations of anxiety related to rehabilitation, future uncertainty, family relationships, social stigma, and psychological distress; (b) a developmental process from fear and reluctance toward acceptance and authentic participation in group counseling; (c) the central role of counselor empathy, unconditional positive regard, and psychological safety in facilitating therapeutic change; (d) psychological and interpersonal improvements reflected in reduced anxiety, stronger emotional regulation, and increased self-confidence; and (e) residents’ recommendations for strengthening counseling programs through more collaborative and humanistic practices. Demographic patterns further indicated that younger residents were more concerned about social stigma and peer judgment, whereas residents with repeated rehabilitation experiences expressed more complex anxiety associated with relapse and unmet expectations. These findings demonstrate that anxiety reduction is a multidimensional process shaped by the interaction of therapeutic relationships, peer support, psychological safety, and residents’ readiness for change. The study contributes practical implications for counseling practice, rehabilitation policy, and future qualitative research on substance use recovery.